Data for: National contributions to climate change mitigation from agriculture: allocating a global target - Richards, Meryl B.; Wollenberg, Eva Karoline; Vuuren, Detlef P. van (Informa UK Limited, 2018)
Supplemental materials, including dataset for article: National contributions to climate change mitigation from agriculture: allocating a global target.